Consumo de frutas no município de Ipanguaçu – RN - Melo, Sérgio Bandeira de (Universidade Federal Rural do Semi-Árido, 2018)
Quality in decision-making to purchase and consume fruit are the main issues of this paper to be distinguished and their possible mutualities with the age bracket, sex, educational attainment and income, a survey of fruit consumers in the city of Ipanguaçu was enhanced, in Rio Grande do Norte state. The methodology used was descriptive, and data were collected through a questionnaire, thus, 100 people were interviewed at the main fruit sales points, as well as supermarkets, public market, fruit house and fair. The presented precepts that could be changeable were: price; appearance, flavor and aroma; packing; offering regularly (product easy to find); brand; lifespan (durability); convenience (easy to carry and use); absence of pesticide residues; source; verification; environment; nutritional value; functional value; enhancement of socio-cultural aspects; among others. Due to the accomplishment of the research and the achieved results, the information shows a magnitude in the paramentation of their choices with fruit that reference base uses considerable percentage, the sequence of the questions were the appearance, taste and flavor, price, nutritional value and lack of pesticides as the five most cited in the highlight of buying fruits caused by consumers from Ipanguaçu city in 2018.
Monografia
Keywords: Pós colheita; Consumidor; Consumo; Qualidade; Post crop; Consumer; Consumption; Quality; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA